Analisis Bentuk Tindak Tutur dalam Teks Video Berbahasa Bali Karya Arykakul Bali: Kajian Pragmatik - Paramartha, Putu Krisna; Suryati, Ni Made; Antara, I Gde Nala (Humanis; Vol 28 No 2 (2024)DO - 10.24843/JH.2024.v28.i02.p10, 2024)
The purpose of this research is to describe the form of speech acts in the text that has been transcribed from the Balinese video by Arykakul Bali. This research uses the theory of pragmatics, especially regarding the form of speech acts according to George Yule. The methods and techniques used are in the stage of providing data, the listening method is used, assisted by the basic technique of tapping and the advanced technique of free listening, and note taking. Then continued with literal and idiomatic translation techniques. At the stage of data analysis, the pragmatic pairing method was used with the basic technique of PUP and the advanced technique of HBMP. At the stage of presenting the results of data analysis, formal and informal methods are used with deductive and inductive techniques. This study took a sample of five videos that have been published on the youtube channel account of Arykakul Bali. The results obtained in this study are the form of speech acts in the Balinese video text by Ary Kakul consisting of 87 direct speech acts and 24 indirect speech acts.